Regional Government Autonomy In Indonesia: The Ambiguity Of The Federalism Or Republic Model - Muhammad Mutawalli Mukhlis; Muhammad Saleh Tajuddin; Dewi Andriani; Rizal Muchtasar; Ahmad Masum (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Syariah and Law, Volume 13 Issue 1 Page (35-57)